First Evidence of Feeding-Induced RNAi in Banana Weevil via Exogenous Application of dsRNA - Shaykins Mwaka, Henry; Christiaens, Olivier; Namanya Bwesigye, Priver; Kubiriba, Jerome; Kateera Tushemereirwe, Wilberforce; Gheysen, Godelieve; Smagghe, Guy (Insects, 2022)
Banana weevil (Cosmopolites sordidus) is the most devastating pest of banana and plantain worldwide, yet current control measures are neither effective, sustainable, nor environmentally sound, and no resistant farmer-preferred cultivars are known to date. In this paper, we examined the ability to induce RNA interference (RNAi) in the banana weevil via feeding. We first developed an agar- and banana corm (rhizome) flour-based artificial diet in a multi-well plate setup that allowed the banana weevils to complete their life cycle from egg through the larval instars to the pupal stage in an average period of 53 days. Adults emerged about 20 days later. The artificial diet allowed the tunneling and burrowing habits of the larvae and successful metamorphosis up to adult eclosion. Adding dsRNA for laccase2 to the artificial diet resulted in albino phenotypes, confirming gene-silencing. Finally, C. sordidus was fed with dsRNA against a selection of essential target genes: snf7, rps13, mad1, vha-a, vha-d, and lgl for a period of 45 days. 100% mortality within 9–16 days was realized with dssnf7, dsrps13, and dsmad1 at 200 ng/mL artificial diet, and this corresponded to a strong reduction in gene expression. Feeding the dsRNA targeting the two vha genes resulted in 100% mortality after about 3–4 weeks, while treatment with dslgl resulted in no mortality above the dsgfp-control and the water-control. Our results have implications for the development of RNAi approaches for managing important crop pests, in that banana weevils can be controlled based on the silencing of essential target genes as snf7, rps13, and mad1. They also highlight the need for research into the development of RNAi for banana protection, eventually the engineering of host-induced gene-silencing (HIGS) cultivars, given the high RNAi efficacy and its species-specific mode of action, adding the RNAi approach to the armory of integrated pest management (IPM).
Keywords: RNA interference (RNAi); Cosmopolites sordidus; Banana weevil; Artificial diet; Pest control; dsRNA feeding